There there - Orange, Tommy, 1982- (2019)
Here is a story of several people, each of whom has private reasons for travelling to the Big Oakland Powwow. Jacquie Red Feather is newly sober and trying to make it back to the family she left behind in shame. Dene Oxendene is pulling his life together after his uncle's death and has come to work at the powwow to honour his uncle's memory. Opal Viola Victoria Bear Shield has come to watch her nephew Orvil Red Feather, who has taught himself traditional Indian dance through YouTube videos and has come to the powwow to dance in public for the very first time. There will be glorious communion, and a spectacle of sacred tradition and pageantry. And there will be sacrifice, and heroism, and unspeakable loss
Reading group guide available at www.ReadingGroupCenter.com -- Back cover
Keywords: Indians of North America -- Fiction; Indians of North America -- Ethnic identity -- Fiction; Indians of North America -- California -- Oakland -- Fiction; Interpersonal relations -- Fiction; Powwows -- Fiction; Group identity -- Fiction; Collective memory -- Fiction; Documentary films -- Production and direction -- Fiction; Identity (Philosophical concept) -- Fiction; Recovering alcoholics -- Fiction; Dysfunctional families -- Fiction; Mass shootings -- Fiction; Oakland (Calif.) -- Fiction; Fiction